Community Decision-Making Pathways and Collective Mechanisms Shaping Economic Resilience in the Spermonde Islands - Hukma Ratu Purnama; Syamsu Nujum; Fadhila Ratu Pratiwi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The Spermonde Islands, a biodiversity-rich coastal area, face escalating ecological and socioeconomic pressures, such as overfishing, pollution, coral bleaching, and shifting fish patterns, which heighten the economic vulnerability of fisher households lacking alternative livelihoods and resilience to climate and economic shocks. This research aims to uncover the community decision-making pathways that shape local economic resilience in post-crisis areas by examining the processes, patterns, and factors that influence community collective decisions in response to ecological pressures and structural change. Using an exploratory qualitative approach based on a case study in the Spermonde Islands, data were collected through in-depth interviews. The results show that local economic resilience is shaped by three main decision paths, namely diversification of livelihoods to reduce vulnerability, strengthening social networks and local institutions as a collective mechanism to face uncertainty, and adjusting coastal resource utilization strategies to ecological change. This study emphasizes that the capacity of communities to make adaptive decisions is an important determinant in maintaining the economic sustainability of the post-crisis region and contributes to the development of community-based economic resilience theories and the formulation of coastal development policies that are responsive to climate change.